2017
DOI: 10.1128/jvi.02325-16
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Specific for the V2, V3, CD4-Binding Site, and gp41 of HIV-1 Mediate Phagocytosis in a Dose-Dependent Manner

Abstract: In light of the weak or absent neutralizing activity mediated by anti-V2 monoclonal antibodies (MAbs), we tested whether they can mediate Ab-dependent cellular phagocytosis (ADCP), which is an important element of anti-HIV-1 immunity. We tested six anti-V2 MAbs and compared them with 21 MAbs specific for V3, the CD4-binding site (CD4bs), and gp41 derived from chronically HIV-1-infected individuals and produced by hybridoma cells. ADCP activity was measured by flow cytometry using uptake by THP-1 monocytic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 67 publications
6
41
1
Order By: Relevance
“…Gas6/protein S might need to synergize with additional signals for efficient phagocytosis of live HIV-1-infected cells. Because broadly neutralizing antibodies against HIV-1 can provide signals for phagocytosis via the Fcreceptor (Musich et al, 2017), it would be of interest to determine whether the broadly neutralizing antibodies can synergize with Gas6/protein S to clear infected cells by phagocytosis/efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gas6/protein S might need to synergize with additional signals for efficient phagocytosis of live HIV-1-infected cells. Because broadly neutralizing antibodies against HIV-1 can provide signals for phagocytosis via the Fcreceptor (Musich et al, 2017), it would be of interest to determine whether the broadly neutralizing antibodies can synergize with Gas6/protein S to clear infected cells by phagocytosis/efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the epitope specificity of Abs mediating ADCP still needs to be investigated. Musich et al demonstrated that anti-V2 monoclonal Abs mediated ADCP activity in a dosedependent manner similar to anti-V3 and CD4bs monoclonal Abs against clade B gp120 (154) but displayed increased activity against clade C gp120 compared to anti-V3 and anti-CD4bs monoclonal Abs, suggesting the broader recognition of exposed epitopes (154); this may also have been due to V2 epitopes being more conserved between clade B and C than V3 epitopes. Moreover, the role played by the cell type that mediates ADCP should also be defined.…”
Section: Antibody-dependent Cellular Phagocytosismentioning
confidence: 99%
“…46,47 Monoclonal Abs were only used after they passed all QC assays. 48 Human BM Samples were obtained from healthy lactating women who had signed informed consents. Milk was expressed using double electronic or manual pumps.…”
Section: Antibodiesmentioning
confidence: 99%